2012
DOI: 10.1007/s10682-012-9577-z
|View full text |Cite
|
Sign up to set email alerts
|

Does variation in host plant association and symbiont infection of pea aphid populations induce genetic and behaviour differentiation of its main parasitoid, Aphidius ervi?

Abstract: International audienceThe host-associated differentiation (HAD) hypothesis states that higher trophic levels in parasitic associations should exhibit similar divergence in case of host sympatric speciation. We tested HAD on populations of Aphidius ervi the main parasitoid of the pea aphid Acyrthosiphon pisum, emerging from host populations specialized on either alfalfa or red clover. Host and parasitoid populations were assessed for genetic variation and structure, while considering geography, host plant and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 98 publications
1
24
0
Order By: Relevance
“…The importance of species and genotype identity on trophic interactions has been demonstrated between insects and plants (Oliver, Moran & Hunter ; Bilodeau et al . ; Cayetano & Vorburger ; Hackett, Karley & Bennett ) and AM fungi and their host plants (Vandenkoornhuyse et al . ; Gange, Brown & Aplin ; Bennett, Alers‐Garcia & Bever ; Jansa, Smith & Smith ; Hempel et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of species and genotype identity on trophic interactions has been demonstrated between insects and plants (Oliver, Moran & Hunter ; Bilodeau et al . ; Cayetano & Vorburger ; Hackett, Karley & Bennett ) and AM fungi and their host plants (Vandenkoornhuyse et al . ; Gange, Brown & Aplin ; Bennett, Alers‐Garcia & Bever ; Jansa, Smith & Smith ; Hempel et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Bilodeau et al . ), all of which might have been affected by differences in plant nutritional quality for M. euphorbiae (Karley, Douglas & Parker ). Further work would be needed to identify precisely the causal factor(s) underlying the effect of AM fungal presence and Solanum type on increased aphid susceptibility to parasitism, and whether it was associated with larger aphid size, enhanced nutritional quality or compromised aphid physiological resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to generating new data for the aforementioned collections (totalling 1932 surveyed aphids), we used data from prior publications on collections from nearby regions to enhance our sample sizes in our targeted locales (Pennsylvania, California and Utah) (Leonardo & Muiru, ; Oliver et al., ; Russell et al., ); we also added data from a new locale, southern Quebec (Bilodeau, Simon, Guay, Turgeon, & Cloutier, ). Aphids from New York and Pennsylvania had typically been collected across multiple times in each of the surveyed years.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are concordant with Bilodeau et al. (2013), which found a lack of host-associated parasitoid populations in introduced populations of A. ervi associated with two specialized host races of the pea aphid A. pisum (alfalfa and red clover host races) in a smaller scale study (between 160–240 km) in North America, using a different set of microsatellites. In addition, other several studies on aphid parasitoids have shown a lack of host-associated genetic differentiation (Lozier et al.…”
Section: Discussionmentioning
confidence: 99%